Do We Belong? A Conceptual Model for International Students’ Sense of Belonging in Community Colleges - García, Hugo A; Garza, Tiberio; Yeaton-Hromada, Katie (Journal of International Students, 2019)
International student enrollment in higher education has risen in the United States for the past several decades. Along with the increase within 4-year institutions, the number of international students at community colleges also continues to rise. Open Doors reports there were 91,648 total international students enrolled in community college for the 2014–2015 academic year. Since student retention is often reviewed as a measure of “the quality of educational experiences” (Lee, 2010, p. 68), these changing enrollment statistics raise questions about international students’ engagement and sense of belonging within U.S. community colleges. Guided by Deil-Amen’s (2011) construct of socio-academic integration moments and Strayhorn’s (2012) sense of belonging, and using the Community College Survey of Student Engagement dataset and structural equation modeling, this study found that socio-academic integration was instrumental for sense of belonging for international students while social integration is also, to a lesser extent, significant to sense of belonging.